Rational design of a novel multi-epitope peptide-based vaccine against Onchocerca volvulus using transmembrane proteins - Shey, Robert Adamu; Ghogomu, Stephen Mbigha; Nebangwa, Derrick Neba; Shintouo, Cabirou Mounchili; Yaah, Ntang Emmaculate; Yengo, Bernis Neneyoh; Nkemngo, Francis Nongley; Esoh, Kevin Kum; Tchatchoua, Nelly Manuela Tatchou; Mbachick, Tekoh Terriss; Dede, Api Fon; Lemoge, Arnaud Azonpi; et al. (Frontiers in Tropical Diseases, 2022)
Almost a decade ago, it was recognized that the global elimination of onchocerciasis by 2030 will not be feasible without, at least, an effective prophylactic and/or therapeutic vaccine to complement chemotherapy and vector control strategies. Recent advances in computational immunology (immunoinformatics) have seen the design of novel multi-epitope onchocerciasis vaccine candidates which are however yet to be evaluated in clinical settings. Still, continued research to increase the pool of vaccine candidates, and therefore the chance of success in a clinical trial remains imperative. Here, we designed a multi-epitope vaccine candidate by assembling peptides from 14 O. volvulus (Ov) proteins using an immunoinformatics approach. An initial 126 Ov proteins, retrieved from the Wormbase database, and at least 90% similar to orthologs in related nematode species of economic importance, were screened for localization, presence of transmembrane domain, and antigenicity using different web servers. From the 14 proteins retained after the screening, 26 MHC-1 and MHC-II (T-cell) epitopes, as well as B-cell epitopes were predicted and merged using suitable linkers. The Mycobacterium tuberculosis Resuscitation-promoting factor E (RPFE_MYCTU), which is a TLR4 agonist, was then added to the N-terminal of the vaccine candidate as an adjuvant. Immune simulation predicted strong B-cell and IFN- based immune responses which are necessary for protection against O. volvulus infection. Molecular docking and molecular dynamic simulation predicted stable interactions between the 3D modeled vaccine candidate with TLR4 as a receptor. These results show that the designed vaccine candidate has the potential to stimulate both humoral and cellular immune responses and should therefore be subject to further laboratory investigation.